Evaluation of critical success factors of 3D printing technology implementation using analytic hierarchy process (AHP) - Shahrubudin, Nurhalida (2021)
The study focused on the Critical Success Factors (CSFs) for implementing 3D printing technology in manufacturing firms of Malaysia. This technology has emerged during recent years as a flexible and powerful technique in advance manufacturing industry. However, while 3D printing technology is beginning to emerge in manufacturing sector, given the lots of benefits, but, more information is needed to progress on ways to enhance adoption. This study aimed to identify the Critical Success Factors (CSFs) for 3D printer technology implementation in manufacturing industry and to evaluate the Critical Success Factors (CSFs) by using Analytic Hierarchy Process (AHP). The process of data collection was obtained using quantitative methods where a set of questionnaires was prepared. 40 experts in 3D printing technology was selected to respond to the questionnaire. There are 9 criteria and 33 sub-criteria for adoption of 3D printing technology in manufacturing industry. Among the 33 sub-criteria, the most important sub-criteria are time taken or speed to produce the 3D printed object, with different type of nozzle and cost of worker prioritized as the second and third sub-criteria. The result shows element technology (0.156) is the most important factor, followed by quality and accuracy (0.150), cost (0.135), and materials (0.133). This study was done to help the company to identify the Critical Success Factors (CSFs) for implementing 3D printing and to evaluate the Critical Success Factors (CSFs) for implementing 3D printing technology in manufacturing firms by using AHP method. The results indicate that technology and quality and accuracy are the most important factors for the implementation of 3D printing. Keywords: 3D printing, implementation, manufacturing, quality, technology